The Effect of Sales and Customer Orientation on Salespeople's Work Performance and the Role of Spiritual Intelligence - Özyurt, Rana; yükselen, cemal; Tosun, Neşe (International Journal of Contemporary Economics and Administrative Sciences, 2024)
Spiritual intelligence has been considered an important concept in studies in recent years. Spiritual intelligence, which is one of the mental capacities contributing to the cognitive and emotional competencies of individuals and providing them with values such as self-knowledge and mastery in mental states, also plays an important role in the work performance of salespeople. In this study, which reveals the role of spiritual intelligence in brands' sales and/or customer orientation depending on their understanding and goals, it is seen that spiritual intelligence does not assume a regulatory role but an important mediating role.